The Dynamics of Islamic Educational Institutions - Abdullah, Burhan; Ansori, M. Afif; Andari, An An (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research aims to explain the dynamics of Mathla'ul Anwar educational institution from an educational aspect. This research type is qualitative with a Library Research approach. The research data consists of data about the dynamics of Mathla'ul Anwar educational institution from the educational aspect from primary sources in the form of books on the dynamics of educational institutions, Mathla'ul Anwar educational institutions, books on institutional development in Islamic education, and relevant journals. Data collection techniques were carried out using documentation studies. The researchers' data sources were obtained from books and journals about the dynamics of Mathla'ul Anwar educational institutions from the educational aspect. Data analysis uses Content Analysis. Based on the research results obtained, Mathla'ul Anwar is an educational institution that emphasizes a holistic approach to developing its students. They integrate educational academies with the formation of moral character and spirituality based on Islamic values. Their curriculum includes general subjects such as mathematics and science, as well as in-depth Islamic religious studies and Arabic. In addition, this institution is active in developing students through various extracurricular activities such as sports, arts, and community service, which aim to develop special skills and social values. Mathla'ul Anwar also pays attention to developing teacher professionalism through continuous training and professional education, ensuring that the teaching delivered remains relevant and in accordance with high educational standards. With their commitment to holistic education and Islamic values, this institution prepares students to become comprehensive individuals of high integrity, ready to face global challenges and contribute positively to society.